OP0099 Modular Repertoire Analysis Identifies Complex Coordinated Type I- Type II Transcriptional Signatures in Adult SLE Patients. (10th June 2014) - Chiche, L.; Jourde-Chiche, N.; Whalen, E.; Dang, K.; Presnell, S.; Gersuk, V.; Nguyen, Q.-A.; Anguiano, E.; Quinn, C.; Dussol, B.; Burtey, S.; Berland, Y.; et al.
Abstract : Background: A pivotal role for Type I interferon (IFN) in SLE is supported by gene expression studies that identified the so-called type I IFN signature (IS). Objectives: The aim of this study was to improve characterization of the blood-IFN signature in adult SLE patients. Methods: Consecutive SLE patients fulfilling the ACR criteria were enrolled and followed-up prospectively. Microarray data were generated using Illumina beadchips. A modular transcriptional repertoire was employed as a framework for the analysis. Results: Our repertoire of 260 modules, which consist of co-clustered gene sets, included 3 IFN-annotated modules (M1.2, M3.4 and M5.12) that were strongly up-regulated in SLE patients. At the individual level, a modular IS (ie, over-expression of at least 1 of the 3 IFN modules) was observed in 54/62 (87%) of patients or 131/157 (83%) of samples. The IFN signature was more complex than expected with each module displaying a distinct activation threshold (M1.2<M3.4<M5.12), thus providing a modular score to stratify SLE patients based on the presence of 0, 1, 2 or 3 active IFN modules. This "gradient" mIS was similarly observed in 2 independent SLE datasets. Samples were then classified in 4 groups according to their individual "modular IFN score" corresponding to the number of up-regulated IFN modules: Absent (0) in 26 (17%), Mild (1) in 17 (11%), Moderate (2) in 68 (43%) and Strong (3) in 46 (29%) samples. No differences in age, gender, ethnicity or disease duration was observed between the 4 groups. Compared to patients with absent/mild mIS, those with moderate/strong mIS had significantly higher anti-dsDNA titers (p=0.03) and lower lymphocyte count (p<0.0001). SLEDAI score was not significantly different between groups, but patients with moderate/strong mIS were less likely to be treated with antimalarials (p=0.002) or with a combination of immunosuppressant and antimalarials (p=0.0006). A similar gradient in mIS was observed within clinically quiescent patients, for whom moderate/strong modular scores (2 or 3 active IFN modules) were associated with higher anti-dsDNA titers and lower lymphocyte count than patients with absent/mild modular scores (0 or 1 active IFN modules). Longitudinal analyses (at least 3 consecutive visits, n=29) showed that whereas module M1.2 was very stable (mean coefficient of variation CV=0.05), M3.4 and M5.12 could vary over time in a single patient (mean CV=0.39 and 0.91 respectively). Interestingly, mining of other datasets suggested that M3.4 and M5.12 could be also driven by INF-b and g. Conclusions: Modular repertoire analysis reveals complex IFN signatures in SLE, not restricted to the previous IFN-a signature, but involving also b and g IFNs. These modular IFN signatures may help in the design of disease activity biomarkers. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2405